Study on Flexural Behavior of Cross-Laminated Timber Based on Different Tree Species - Weidong Lu; Jiahui Gu; Bibo Wang (Advances in Materials Science and Engineering)
The flexural behavior of CLT panels was experimentally studied. The effects of number of layers, thickness and wood combination on the failure modes, ultimate bearing capacity, stiffness, and ductility of the specimen were analyzed. The test results showed that the flexural strength of the hybrid CLT specimens was basically unchanged, but the stiffness increased by 8% to 22% compared with the CLT specimens of all poplar wood. Compared with the CLT of the whole Douglas fir, the failure mode of the hybrid specimens changes from brittle shear failure to ductile bending failure. Furthermore, the calculation formula of the bending bearing capacity under various failure modes was proposed. The analytical results agreed well with the test results.